2019
DOI: 10.1016/j.ecolmodel.2019.108737
|View full text |Cite
|
Sign up to set email alerts
|

CO2 fertilization plays a minor role in long-term carbon accumulation patterns in temperate pine forests in the southwestern Pyrenees

Abstract: Isolating the long-term fertilization effect of CO2 from other climate-and site-related effects on tree growth has been proven a challenging task. To isolate long-term effects of [CO2] on water use efficiency at ecosystem level, we used the FORECAST Climate forest model, calibrated for Scots pine (Pinus sylvestris L.) forests in the southwestern Pyrenees, growing at a Mediterranean montane site and at a continental subalpine site. Future climate scenarios (RCP 4.5 and RCP 8.5) were generated using a battery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…Whereas increasing atmospheric CO 2 concentrations might directly promote forest productivity and growth (e.g. Keenan et al, 2011), this effect will be strongly modulated by increasing temperatures and drought conditions (Bussotti et al, 2014; Doblas‐Miranda et al, 2017; Lo et al, 2019; Penuelas et al, 2011). This might partly explain why median projected trends for the ‘materials and assistance’ category were more negative for scenarios below the Paris Agreement (Figure 2b), under which CO 2 forcing is smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas increasing atmospheric CO 2 concentrations might directly promote forest productivity and growth (e.g. Keenan et al, 2011), this effect will be strongly modulated by increasing temperatures and drought conditions (Bussotti et al, 2014; Doblas‐Miranda et al, 2017; Lo et al, 2019; Penuelas et al, 2011). This might partly explain why median projected trends for the ‘materials and assistance’ category were more negative for scenarios below the Paris Agreement (Figure 2b), under which CO 2 forcing is smaller.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) simulated competition for nutrient, light and water in mixed conifer-broadleaf forests, whereas in this issue Lo et al (2019) demonstrated the low impact of increased CO2 availability in the productivity of pine forests. Both works used FORECAST Climate.…”
Section: Introductionmentioning
confidence: 89%
“…For this reason, they represent promising prospects for understanding and predicting forest ecosystems functioning changes. Studies have already tried to predict trends of forest productivity (Madani et al, 2018;Prislan et al, 2019;Tei et al, 2017), carbon storage (Gustafson et al, 2017;Lindner et al, 2014;Lo et al, 2019) or C, H2O and N dynamics (Dong et al, 2019) in the decades to come.…”
Section: Process-based Model Prediction In Context Of Global Changementioning
confidence: 99%